2020
DOI: 10.1177/0957650920954967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inlet guide vane and blade pitch angles on the performance of a submersible axial-flow pump

Abstract: This study investigates the effects of inlet guide vane (IGV) and blade pitch angles on the steady and unsteady performance of a submersible axial-flow pump. To analyze the interaction between the IGVs and the rotor blades, both steady and unsteady three-dimensional Reynolds-averaged Navier-Stokes equations were used with shear stress transport turbulence closure. Hexahedral meshes were used in the computational domain. The numerical results for performance curves showed good agreement with experimental data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…According to Yang et al 7 , the research pump model includes eleven conical-tip symmetrical IGVs. The Kim et al 5 and Nguyen et al 6 studies include an IGV taking the form of a simple blade rounded at the leading edge (LE) and trailing edge (TE) with constant thickness. Furthermore, in the studies of Feng et al 3 and Guo et al 4 , the shape of the IGV is rather rudimentary, with a rectangular profile.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yang et al 7 , the research pump model includes eleven conical-tip symmetrical IGVs. The Kim et al 5 and Nguyen et al 6 studies include an IGV taking the form of a simple blade rounded at the leading edge (LE) and trailing edge (TE) with constant thickness. Furthermore, in the studies of Feng et al 3 and Guo et al 4 , the shape of the IGV is rather rudimentary, with a rectangular profile.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [11] combined numerical simulations and experimental verification to reveal the development process of the skewed flow characteristics inside the S-shaped channel of a 15-degree slanted axial flow pump. Kim et al [12] found that the steady and unsteady performance characteristics of a submersible axial flow pump depend on the inlet guide vanes (IGV) and blade pitch angle. Zhou et al [13] improved the internal flow characteristics of an axial flow pump under low flow conditions by adopting a double-inlet structure and combining numerical simulations with experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is urgent to study the three-dimensional dynamic flow inside the vertical axial flow pump device. Many scholars in China and abroad have carried out a lot of research work, and the main research contents are focused on the analysis of the three-dimensional flow field inside the axial flow pump device [2][3][4][5] and the numerical analysis of the internal pressure pulsation of the axial flow pump device [6][7][8]. Study on three-dimensional shape optimization of axial flow pump device flow structure [9][10][11]; the mechanism of cavitation flow in axial flow pump device [12,13], and the influence of inflow conditions on the flow and pulsation characteristics of axial flow pump device [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Chaoyue Wang et al [4] found that there was a flow deviation phenomenon in the S-shaped channel of the slanted axial flow pump, and carried out numerical simulation research and field measurement on the test bench to clarify the mechanism of this phenomenon. Kim Youn Sung et al [5] explored the influence of inlet guide vane and blade angle on three-dimensional steady and unsteady flow of submersible axial flow pump. Ahmed Ramadhan Al-Obaidi et al [6] studied the pressure pulsation of axial flow pump and analyzed the relationship between pressure pulsation and cavitation.…”
Section: Introductionmentioning
confidence: 99%